Historicizing Fear Ignorance, Vilification, and Othering - Boyce, Travis D.; Chunnu, Winsome M. (University Press of Colorado, 2020)
Historicizing Fear is a historical interrogation of the use of fear as a tool to vilify and persecute groups and individuals from a global perspective, offering an unflinching look at racism, fearful framing, oppression, and marginalization across human history. The book examines fear and Othering from a historical context, providing a better understanding of how power and oppression are used in the present day.Contributors ground their work in the theory of Othering-the reductive action of labeling a person as someone who belongs to a subordinate social category defined as the Other-in relation to historical events, demonstrating that fear of the Other is universal, timeless, and interconnected. Chapters address the music of neo-Nazi white power groups, fear perpetuated through the social construct of black masculinity in a racially hegemonic society, the terror and racial cleansing in early twentieth-century Arkansas, the fear of drug-addicted Vietnam War veterans, the creation of fear by the Tang Dynasty, and more.Timely, provocative, and rigorously researched, Historicizing Fear shows how the Othering of members of different ethnic groups has been used to propagate fear and social tension, justify state violence, and prevent groups or individuals from gaining equality. Broadening the context of how fear of the Other can be used as a propaganda tool, this book will be of interest to scholars and students of history, anthropology, political science, popular culture, critical race issues, social justice, and ethnic studies, as well as the general reader concerned with the fearful framing prevalent in politics.Contributors: Quaylan Allen, Melanie Armstrong, Brecht De Smet, Kirsten Dyck, Adam C. Fong, Jeff Johnson, Łukasz Kamieński, Guy Lancaster, Henry Santos Metcalf, Julie M. Powell, Jelle Versieren